The Other Wes Moore Faculty Guide - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
This guide provides background knowledge related to "The Other Wes Moore," and its topics for Kansas State University professors and faculty to use within their classes and on campus. Included in the guide are a timeline of the characters' lives, discussion questions, thematic information, similar titles, and on-campus resources.
Keywords: The Other Wes Moore; Guide; Faculty development; Common reading program; First-year experience program; Application of learning; Brochures